2011
DOI: 10.1097/yct.0b013e3181e631a8
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, Mood, and Electroencephalographic Effects of Noninvasive Cortical Stimulation With Weak Electrical Currents

Abstract: : Here, we show no neurophysiological or behavioral signs that transcranial DC stimulation or AC stimulation with weak currents induce deleterious changes when comparing active and sham groups. This study provides therefore additional information for researchers and ethics committees, adding important results to the safety pool of studies assessing the effects of cortical stimulation using weak electrical currents. Further studies in patients with neuropsychiatric disorders are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 41 publications
5
45
0
1
Order By: Relevance
“…Nitsche et al 2012;Peña-Gómez et al 2011;Plazier et al 2012;Vanderhasselt et al 2013), although Fregni et al (2008) completed the final evaluation approximately 10 min after stimulation cessation, while Tadini et al (2011) Batsikadze et al 2013). It is possible that the convention timing of re-assessment following tDCS does not allow for a sufficient period to detect tDCS-induced modulations of mood.…”
Section: Discussionmentioning
confidence: 99%
“…Nitsche et al 2012;Peña-Gómez et al 2011;Plazier et al 2012;Vanderhasselt et al 2013), although Fregni et al (2008) completed the final evaluation approximately 10 min after stimulation cessation, while Tadini et al (2011) Batsikadze et al 2013). It is possible that the convention timing of re-assessment following tDCS does not allow for a sufficient period to detect tDCS-induced modulations of mood.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations here are similar to previous findings. There have been rare reports of mild electrical "shock" occurring with no injury during tES which is associated with abrupt making or breaking of the stimulating circuit [21,28,47].…”
Section: Withdrawal and Serious Adverse Eventsmentioning
confidence: 99%
“…Based on prior trials [21,28,47], we developed a comprehensive adverse-event monitoring plan, and implemented conservative (preventative) study withdrawal criterion. We typically could not distinguish between adverse effects and adverse event,…”
Section: General Observations and Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…In an animal study of safety, Liebetanz et al 14 showed, in an animal study of safety, that cathodal-induced brain lesions only occurred when the stimulation intensities almost one hundred times higher than used in clinical studies. In addition, tDCS does not adversely affect brain and heart activity, respectively measured using EEG and EKG records [15][16][17] . In fact, the only adverse effect particularly associated with tDCS is skin redness 18 -even though, this effect is mild and does not seem to compromise blinding in sham-controlled tDCS trials 19 , which consist in turning off the device after < 30-60 seconds of stimulation, remaining turned off until the end of the session 20 .…”
Section: Introductionmentioning
confidence: 99%